Memahami Penggunaan Teknologi Efektif dalam Supervisi Lembaga Pendidikan - Lukman Hakim (Menara Tebuireng, 2016)
Education and learning continue to evolve according to the changing times especially in the field of flow technology, educational institutions in this case should follow the changes in the existing technology in order to keep up with changes to the terms adapted to the needs of education itself. Technological supervision of one of them as additional (supplement), complement (complement), enrichment (enrichment), and substitute (substitution) traditional learning system as outlined in the curriculum. A supervisor should have the competence of the ability to master new technologies, resulting in the implementation of supervision are able to apply supervision accordance with their competence